Analisis Penggunaan Aplikasi Dompet Digital di UMKM Kota Depok - Restu Jati Saputro; Dewi Winarni (Administratif Profesional, 2023)
The payment system, in particular, has undergone major changes as a result of the growing use of information and communication technologies. The development of digital wallets, which enable financial transactions without the need for currency, is one of the improvements in the payment system. This study intends to examine how MSMEs in Depok City use digital wallets. Data are gathered through surveys and interviews with a variety of respondents as part of this research approach, which combines qualitative and quantitative methodologies. This study examined the social, technological, and environmental elements that affect the adoption of digital wallets based on the analysis's findings. The findings of this study suggest that MSMEs in Depok City are not using digital wallets to their full potential. Cash payments are regarded as being easier to use, and MSMEs have not expressed any interest in or motivation to adopt digital wallets. This study suggests initiatives to raise public awareness and better instruct the populace about the advantages and security of utilizing digital wallets in order to promote GNNT. Furthermore, it is also regarded as necessary for the government and business to play a part in creating a solid infrastructure for technology and robust consumer protection systems.The findings of this study are anticipated to shed light on the variables influencing the adoption of digital wallets in Depok City and offer recommendations for developing local digital payment technology policy. Keywords: E-Wallet, System Payment, Information Technology, UMKM